MACHINE RELIABILITY CONTROL BASED ON ECONOMIC CRITERIA - Igor A. Khozyayev; Victor V. Radin (Advanced Engineering Research, 2011)
The technique of separating the part directly relating to reliability from the machine production cost is presented. It enables to operate machine reliability at the production stage. The technique is formalized, and it can be applied to any engineering products.